Influence of Mn-Ni alloying elements on surface film and pitting resistance of Cr-Mn austenitic stainless steels. (30th October 2016) - Qu, H.P.; Chen, H.T.; Lang, Y.P.
Graphical abstract: Highlights: Fe, Cr, Mn oxide layer and passive film thickness of LH was the lowest. Mn enrichment was observed in LH passive film. Surface Mn oxide and sulfide percentage in LH passive film was the highest. Harmful effect of Mn on pitting resistance was more obvious at 60 °C. Appropriate Mn/Ni mass ratio should not be higher than 1.7. Abstract: This research focused on surface film and corrosion resistance of three commercial type 200 austenitic stainless steels including L4, L1 and LH with different Mn/Ni mass ratio in Chinese market. X-ray photoelectron spectrum (XPS) results showed that Fe, Cr and Mn oxide layer thickness and passive film thickness were reduced as Mn/Ni mass ratio increased. Mn enrichment was only found in LH passive film. Mn oxide percentage in LH passive film was also the highest. These disadvantages deteriorated pitting resistance of LH, which was proved by anodic polarization result. Mn/Ni mass ratio should not be higher than 1.7 to ensure good corrosion resistance and low raw material cost.